Research Progress on Stimulus-Responsive Polymer Nanocarriers for Cancer Treatment - Shicui Luo; Zhuo Lv; Qiuqiong Yang; Renjie Chang; Junzi Wu (Pharmaceutics, 2023)
As drug carriers for cancer treatment, stimulus-responsive polymer nanomaterials are a major research focus. These nanocarriers respond to specific stimulus signals (e.g., pH, redox, hypoxia, enzymes, temperature, and light) to precisely control drug release, thereby improving drug uptake rates in cancer cells and reducing drug damage to normal cells. Therefore, we reviewed the research progress in the past 6 years and the mechanisms underpinning single and multiple stimulus-responsive polymer nanocarriers in tumour therapy. The advantages and disadvantages of various stimulus-responsive polymeric nanomaterials are summarised, and the future outlook is provided to provide a scientific and theoretical rationale for further research, development, and utilisation of stimulus-responsive nanocarriers.